(untitled) (Journal of Economic Research & Business Administration, 2015)
The automated system provides the better decision-making, connected with bank risk at delivery of credits, investments and securities, at the expense of special procedures of processing of all information available in system. Use of the automated system allows to raise considerably quality of servicing of bank that is especially important in the conditions of a real competition.